Selective Maintenance in Visual Working Memory Does Not Require Sustained Visual Attention - Hollingworth, Andrew (2012)
In four experiments, we tested whether sustained visual attention is required for the selective maintenance of objects in VWM. Participants performed a color change-detection task. During the retention interval, a valid cue indicated the item that would be tested. Change detection performance was higher in the valid-cue condition than in a neutral-cue control condition. To probe the role of visual attention in the cuing effect, on half of the trials, a difficult search task was inserted after the cue, precluding sustained attention on the cued item. The addition of the search task produced no observable decrement in the magnitude of the cuing effect. In a complementary test, search efficiency was not impaired by simultaneously prioritizing an object for retention in VWM. The results demonstrate that selective maintenance in VWM can be dissociated from the locus of visual attention.